Comparison of Dilution, Filtration, and Microwave Digestion Sample Pretreatments in Elemental Profiling of Wine by ICP-MS - Joshua Godshaw; Helene Hopfer; Jenny Nelson; Susan E. Ebeler (Molecules, 2017)
Wine elemental composition varies by cultivar, geographic origin, viticultural and enological practices, and is often used for authenticity validation. Elemental analysis of wine by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) is challenging due to the potential for non-spectral interferences and plasma instability arising from organic matrix components. Sample preparation mitigates these interferences, however, conflicting recommendations of best practices in ICP-MS analysis of wine have been reported. This study compared direct dilution, microwave-assisted acid digestion, and two filtration sample pretreatments, acidification prior to filtration and filtration followed by acidification, in elemental profiling of one white and three red table wines by ICP-MS. Of 43 monitored isotopes, 37 varied by sample preparation method, with significantly higher results of 17 isotopes in the microwave-digested samples. Both filtration treatments resulted in lower results for 11 isotopes compared to the other methods. Finally, isotope dilution determination of copper based on natural abundances and the 63Cu:65Cu instrument response ratio agreed with external calibration and confirmed a significant sample preparation effect. Overall, microwave digestion did not compare favorably, and direct dilution was found to provide the best compromise between ease of use and result accuracy and precision, although all preparation strategies were able to differentiate the wines.